Imaging meningeal inflammation in CNS autoimmunity identifies a therapeutic role for BTK inhibition - Bhargava, Pavan; Kim, Sol; Reyes, Arthur A; Grenningloh, Roland; Boschert, Ursula; Absinta, Martina; Pardo, Carlos; Zijl, Peter Van; Zhang, Jiangyang; Calabresi, Peter A (Brain (London, England : 1878), 2021)
Leptomeningeal inflammation in multiple sclerosis is associated with worse clinical outcomes and greater cortical pathology. Despite progress in identifying this process in multiple sclerosis patients using post-contrast fluid-attenuated inversion recovery imaging, early trials attempting to target meningeal inflammation have been unsuccessful. There is a lack of appropriate model systems to screen potential therapeutic agents targeting meningeal inflammation. We utilized ultra-high field (11.7 T) MRI to perform post-contrast imaging in SJL/J mice with experimental autoimmune encephalomyelitis induced via immunization with proteolipid protein peptide (PLP139-151) and complete Freund's adjuvant. Imaging was performed in both a cross-sectional and longitudinal fashion at time points ranging from 2 to 14 weeks post-immunization. Following imaging, we euthanized animals and collected tissue for pathological evaluation, which revealed dense cellular infiltrates corresponding to areas of contrast enhancement involving the leptomeninges. These areas of meningeal inflammation contained B cells (B220+), T cells (CD3+) and myeloid cells (Mac2+). We also noted features consistent with tertiary lymphoid tissue within these areas, namely the presence of peripheral node addressin-positive structures, C-X-C motif chemokine ligand-13 (CXCL13)-producing cells and FDC-M1+ follicular dendritic cells. In the cortex adjacent to areas of meningeal inflammation we identified astrocytosis, microgliosis, demyelination and evidence of axonal stress/damage. Since areas of meningeal contrast enhancement persisted over several weeks in longitudinal experiments, we utilized this model to test the effects of a therapeutic intervention on established meningeal inflammation. We randomized mice with evidence of meningeal contrast enhancement on MRI scans performed at 6 weeks post-immunization, to treatment with either vehicle or evobrutinib [a Bruton tyrosine kinase (BTK) inhibitor] for a period of 4 weeks. These mice underwent serial imaging; we examined the effect of treatment on the areas of meningeal contrast enhancement and noted a significant reduction in the evobrutinib group compared to vehicle (30% reduction versus 5% increase; P = 0.003). We used ultra-high field MRI to identify areas of meningeal inflammation and to track them over time in SJL/J mice with experimental autoimmune encephalomyelitis, and then used this model to identify BTK inhibition as a novel therapeutic approach to target meningeal inflammation. The results of this study provide support for future studies in multiple sclerosis patients with imaging evidence of meningeal inflammation.